2019
DOI: 10.15420/icr.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Percutaneous Coronary Intervention in Women: Are There Differences When Compared with Men?

Abstract: Despite advances in the diagnosis and treatment of coronary artery disease, there remains evidence of a disparity in the outcomes for women when compared with men. This article provides a review of the evidence for this discrepancy and discusses some of the potential contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
(61 reference statements)
0
19
0
1
Order By: Relevance
“…Finally, we did not take into account any other non-laboratory clinical factors for the risk stratification of in-hospital mortality, including age and sex, cardiac function, duration of ischemia, and perioperative complications. Especially, it has been reported that there were some sex-differences in outcomes after AMI and their predictive markers [41][42][43], however, we could not tease out any sex-dependent issues due to a limited proportion of female population in our cohorts. Although our risk score model showed a performance comparable to that of the GRACE score, further research is thus needed to assess whether the other clinical factors could increase the predictive value for outcome in patients with STEMI.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, we did not take into account any other non-laboratory clinical factors for the risk stratification of in-hospital mortality, including age and sex, cardiac function, duration of ischemia, and perioperative complications. Especially, it has been reported that there were some sex-differences in outcomes after AMI and their predictive markers [41][42][43], however, we could not tease out any sex-dependent issues due to a limited proportion of female population in our cohorts. Although our risk score model showed a performance comparable to that of the GRACE score, further research is thus needed to assess whether the other clinical factors could increase the predictive value for outcome in patients with STEMI.…”
Section: Discussionmentioning
confidence: 79%
“…Gender-based outcome studies in ACS patients after PCI reported vague results. These studies have shown worse in-hospital and long-term clinical outcomes among females compared with males, especially higher rates of recurrent events during long-term follow-up (Josiah and Farshid, 2019; Kurlansky et al, 2017;Rao et al, 2019;Vasudevan et al, 2018). The role of thromboxane, especially in males and females, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, females showed a higher dh-TxB2 level at baseline as well as at 6 months follow-up when compared to post-PTCA males (Lopez et al, 2014). Prior studies have reported that female patients with ACS undergoing PCI differ from male participants in some baseline characteristics; females are more frequently older with a high prevalence of coronary risk factors, such as diabetes mellitus, hypertension, renal insufficiency, higher prevalence of advanced heart failure, smaller access, lower estimated glomerular filtration rate, higher CAD risk profile, and high rate of bleeding complications as compared with males (Guo et al, 2018;Johansson et al, 2017;Rao et al, 2019). The socioeconomic factor was also linked to a higher risk of recurrent events, i.e., females may delay hospital visits and revascularization therapy compare to males (Lopez et al, 2014;Kareem et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations